A275 REVISITING THE DIAGNOSTIC YIELD OF ERCP BRUSH CYTOLOGY FOR INDETERMINATE BILIARY STRICTURES. (26th February 2020) - Nur, A; Boerner, S; Edwards, L; Ryan, K; James, P
Abstract: Background: Endoscopic Retrograde Cholangiopancreatography (ERCP) brush cytology is the most frequently used tool for sampling indeterminate biliary strictures. Previous studies have demonstrated that the diagnostic yield of brush cytology for malignant biliary strictures is 60%. With improved diagnostic tools, sampling techniques and specimen processing, the yield of ERCP brush cytology may be higher. Aims: To assess the diagnostic yield of ERCP brush cytology in patients with indeterminate biliary strictures and to determine factors associated with positive diagnosis. Methods: This is a retrospective study of all patients who underwent ERCP with brush cytology at University Health Network (UHN) from October 2016 to September 2019. The cytological samples were taken as follows: the cytology brush is introduced into the stricture ten times under direct fluoroscopy guidance. The brush was cut and placed into a methanol based buffered solution (CytoLyt®). Residual sample was then flushed out of the catheter with the solution and into the sample container. Patient demographic, clinical, procedural and pathological data was collected by chart review. All patients were followed for a minimum of three months after their index ERCP. Post-ERCP sampling via repeat ERCP brushings, endoscopic ultrasound fine needle biopsy, percutaneous biopsy or surgical resection was recorded. Results: A total of 97 patients underwent ERCP with brush cytology during the study period (43 females, median age 69 years). Fifty-nine patients (84%) were diagnosed with malignancy via ERCP brush cytology. Using follow up sampling, surgical resection and clinical follow up as the gold standard, the sensitivity, specificity, positive predictive value, negative predictive value and accuracy were 84%, 100%, 100%, and 71% respectively. Patient demographics, degree of cholestasis or stricture location had no significant impact on these outcomes. Conclusions: This study shows a high diagnostic yield for ERCP with brush cytology for patients with indeterminate biliary strictures. Large prospective studies using updated tools, techniques and specimen handling processes are needed to confirm our observations. Funding Agencies: None